Histidine piezoelectric material constructed through chiral strategy and preparation method and application of histidine piezoelectric material
By introducing chiral histidine cations into the crown ether system, the 18-crown ether-6-based amino acid crown ether inclusion compound with excellent piezoelectric properties was solved, and the problem of low electromechanical conversion efficiency of existing materials was achieved. Significantly improved electrical and piezoelectric properties, suitable for a variety of high sensitivity sensing and wearable devices.
Patent Information
- Application Number
- CN202411568377.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The existing crown ether supramolecular rotor has low electromechanical conversion efficiency, making it difficult to develop materials with excellent piezoelectric properties.
Through chiral strategy, L-, D- and DL-histidine cations were introduced into the crown ether system, three amino acid crown ether inclusions based on 18-crown ether-6 were synthesized, utilizing the ferroelectricity and pressure of these materials. The electrical properties are different to design materials with excellent piezoelectric properties.
The good piezoelectric properties and potential ferroelectric properties of three amino acid crown ether inclusions have been achieved, providing new ideas and directions for ferroelectric identification or sensing, and the materials are easy to prepare and easy to operate, suitable for wearable Equipment and other applications.
Smart Images

Figure CN119431814A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the technical field of piezoelectric materials, and in particular relates to a histidine piezoelectric material constructed by a chiral strategy, and a preparation method and application thereof. Background Art
[0002] Piezoelectric materials have a remarkable ability to achieve bidirectional conversion of mechanical force and electrical energy. When these materials are subjected to mechanical pressure, they generate electric charge, and when an electric field is applied, they undergo mechanical deformation. This unique property is the result of the asymmetric distribution of positive and negative charges within the lattice structure of such materials. Since piezoelectricity is a subclass of ferroelectricity, excellent piezoelectric performance is inseparable from ferroelectricity. In recent decades, molecular piezoelectric materials have been widely used in biosensors, dynamic actuators, energy harvesters and other fields due to their unique advantages such as light weight, biocompatibility, mechanical flexibility and environmentally friendly processing.
[0003] In this context, crown ether supramolecular rotators, as an important branch of artificial molecular machines, are usually used as platforms for constructing molecular ferroelectric and piezoelectric materials. In particular, supramolecular inclusion complexes with 18-crown ether-6 as the main body have been widely used in molecular recognition, phase change materials, and even supramolecular polymer gels due to their strong binding force and ability to form complexes with fixed orientation. More importantly, this stator-rotor type structure facilitates energy conversion processes, such as the conversion between thermal energy and kinetic energy, and the conversion between mechanical energy and electrical energy. However, the electromechanical conversion efficiency of this supramolecular rotator is still very low, so mining new analogs with excellent piezoelectricity has become a continuous challenge.
[0004] Benefiting from the structural diversity and tunability of the crown ether-based supramolecular family, the piezoelectric properties of existing crown ether molecules can be significantly improved by optimizing the chemical modification strategy by screening different organic cations and inorganic anions to assemble with crown ether molecules. For example, Li et al. reported that [(histamine)(18-crown-6) 2 ](BF 4 ) 2 By doubly protonating histamine and increasing [(histamine)(18-crown-6)](BF 4 ) successfully imparted piezoelectricity, but its d 33 5pCN -1 Recently, based on H / F substitution, Lv and co-workers revealed a crown ether-based supramolecular rotator that achieved a piezoelectric coefficient d 33The significant enhancement is more than 40 times greater than that of non-fluorinated compounds. However, the reported crown ether supramolecular rotators still show poor electromechanical conversion properties, but it is reported that the material coupling polar structure and ferroelectricity has been shown to be the key to achieving excellent piezoelectric response. Therefore, it is necessary to develop new piezoelectric materials. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a histidine piezoelectric material constructed by a chiral strategy and a preparation method thereof.
[0006] The present invention is achieved by introducing L-, D- and DL-histidine cations into the crown ether system using a chiral strategy to obtain three amino acid crown ether inclusion complexes [L-His-OMe] based on 18-crown ether-6. 2+ (18-crown-6)[CoCl 4 ] 2- (1) [D-His] 2+ [(18-crown-6)(H 2 O)][CoCl 4 ] 2- (2) and [DL-His] 2+ (18-crown-6)[CoCl 4 ] 2- (3) All three have good piezoelectric properties and potential ferroelectricity.
[0007] Another object of the present invention is to provide a method for constructing a histidine piezoelectric material by a chiral strategy, and to obtain a blue compound 1-3 by natural evaporation from a methanol aqueous solution;
[0008] Compound 1 is [L-His-OMe] 2+ (18-crown-6)[CoCl 4 ] 2- ;
[0009] Compound 2 is [D-His] 2+ [(18-crown-6)(H 2 O)][CoCl 4 ] 2- ;
[0010] Compound 3 is [DL-His] 2+ (18-crown-6)[CoCl 4 ] 2- .
[0011] The synthesis method of compound 1 is as follows: 234 mg (1.51 mmol) of L-histidine, 400 mg (1.51 mmol) of 18-crown ether and CoCl2 6H 2 360 mg (1.51 mmol) of O was dissolved in 10 mL of methanol, 5 mL of methanol and 10 mL of methanol respectively, and then 1 mL of hydrochloric acid (mass fraction 36.5%) was added dropwise to the L-histidine and cobaltous chloride mixed solution for acidification, and the acidified mixed solution was sonicated until the solution was clear, and then the cobaltous chloride mixed solution and the 18-crown ether-6 mixed solution were added dropwise to the L-histidine mixed solution respectively, and then the mixed solution was placed at room temperature and waited for natural evaporation, and blue strip crystals 1 were obtained after 7 days;
[0012] The synthesis method of compound 2 is as follows: 234 mg (1.51 mmol) of D-histidine, 400 mg (1.51 mmol) of 18-crown ether and CoCl 2 6H 2 360 mg (1.51 mmol) of O was dissolved in 10 mL of methanol, 5 mL of methanol and 10 mL of methanol respectively, and then 1 mL of hydrochloric acid (mass fraction 36.5%) was added dropwise to the mixed solution of D-histidine and cobaltous chloride respectively for acidification. The acidified mixed solution was sonicated until the solution was clear, and then the cobaltous chloride mixed solution and the 18-crown ether-6 mixed solution were added dropwise to the D-histidine mixed solution respectively, and then the mixed solution was placed at room temperature and waited for natural evaporation. After 7 days, blue strip crystals 2 were obtained;
[0013] The synthesis method of compound 3 is as follows: 234 mg (1.51 mmol) of DL-histidine, 400 mg (1.51 mmol) of 18-crown ether and CoCl 2 6H 2 O 360 mg (1.51 mmol) was dissolved in 10 mL methanol, 5 mL methanol and 10 mL methanol respectively, and then 1 mL hydrochloric acid (mass fraction 36.5%) was added dropwise to the mixed solution of DL-histidine and cobaltous chloride for acidification. The acidified mixed solution was sonicated until the solution was clear, and then the cobaltous chloride mixed solution and the 18-crown ether-6 mixed solution were added dropwise to the DL-histidine mixed solution in sequence, and then the mixed solution was placed at room temperature and waited for natural evaporation. After 7 days, blue strip crystals 3 were obtained.
[0014] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0015] First, crown ether inclusion compounds are a type of molecular motor machine formed by hydrogen bonds with amine compounds as rotor structures and crown ethers as stators. These compounds tend to have good performance under temperature stimulation, but are not easy to produce ferroelectricity, because a material must meet basic conditions to become a ferroelectric, such as undergoing a reversible structural phase transition, and the ferroelectric phase must crystallize into 10 polar point groups (C 1 , C 2 , C s , C 2V , C 4 , C 4V , C 3 , C 3V , C 6 and C 6V ), and has a standard polarization hysteresis loop. Therefore, crown ether-based molecular ferroelectric materials are very rare. The present invention introduces polar DL-histidine containing an imidazole group in the side chain into the crown ether inclusion system to enhance its polarity, and the overall unit crystallizes in the polar-ferroelectric space group; and synthesizes the enantiomer L-histidine and D-histidine crown ether inclusion complex based on the ferroelectric racemic mixture DL-histidine through a chiral strategy: [L-His-OMe] 2+ (18-crown-6)[CoCl 4 ] 2- (1) [D-His] 2+ [(18-crown-6)(H 2 O)][CoCl 4 ] 2- (2) and [DL-His] 2+ (18-crown-6)[CoCl 4 ] 2- (3) (His = histidine). Crystal structure analysis and circular dichroism (CD) spectroscopy confirmed that compounds 1-3 are polar, with space groups P2 1 , P2 1 2 1 2 1 and Pna2 1 Through the analysis of the test results, it can be seen that the three have similar properties, including the same ferroelectric phase transition temperature and similar dielectric and ultraviolet absorption, but the ferroelectric and piezoelectric properties of the three are quite different. Therefore, the introduction of chiral amino acids into the molecular system can directly design molecular ferroelectrics. The obvious differences in piezoelectric and ferroelectric properties between their enantiomers and racemates may play an important role in future ferroelectric recognition or sensing.
[0016] The present invention uses variable temperature X-ray single crystal diffraction to show that only L- or D-His exists alone in compounds 1 and 2, while L- and D-His exist simultaneously in compound 3, inducing disorder in the molecule. And because DL-His contains both L- and D-His, the intermolecular forces, ferroelectricity, and piezoelectricity of compound 3 will produce a certain "offset" compared with compounds 1 and 2. This obvious difference in piezoelectric and ferroelectric properties between enantiomers and racemates may play an important role in future ferroelectric recognition or sensing. In addition, this work enriches the host-guest amino acid crown ether-based piezoelectric family, and points out an effective strategy for the chemical design of piezoelectricity and even ferroelectricity of host-guest inclusion complexes, providing a theoretical basis for the design of crown ether-based supramolecular piezoelectric materials with good biocompatibility.
[0017] Second, the expected benefits and commercial value after the transformation of the technical solution of the present invention are as follows: Crown ether supramolecules with a host-guest structure are widely used in the fields of photon detectors, chiral optics and spin electronics due to their structural flexibility.
[0018] The technical solution of the present invention fills the technical gap in the industry at home and abroad: L-, D- and DL-histidine cations are introduced into the crown ether system by using a chiral strategy, and three amino acid crown ether inclusion complexes based on 18-crown ether-6 are obtained for the first time:
[0019] [L-His-OMe] 2+ (18-crown-6)[CoCl 4 ] 2- (1);
[0020] [M-[D-His] 2+ [(18-crown-6)(H 2 O)][CoCl 4 ] 2- (2);
[0021] [DL-His] 2+ (18-crown-6)[CoCl 4 ] 2- (3) (His = histidine).
[0022] The technical solution of the present invention solves a technical problem that people have been eager to solve but have never been successful: although the structures of many crown ether host-guest inclusion complexes have been reported, their chirality and piezoelectric properties have rarely been developed so far, let alone ferroelectricity. For this reason, it is an urgent and important task to design chiral host-guest inclusion complex materials and further study their piezoelectric and even ferroelectric properties. The technical solution designs and synthesizes L-histidine and D-histidine crown ether inclusion complexes based on DL-histidine crown ether inclusion complexes. All three have rare ferroelectricity, which provides new ideas and directions for subsequent research.
[0023] The technical solution of the present invention overcomes the technical prejudice: molecular ferroelectrics and piezoelectrics are usually crystalline materials. To be a piezoelectric, a crystalline material must adopt one of 20 non-centrosymmetric point groups, and their structure is determined not only by the molecular symmetry but also by their crystal packing, which should be considered as a more critical factor. For a long time, the vast majority of excellent and advanced ferroelectrics were based on inorganic ceramics and polymers, such as BaTiO 3 (BTO), Pb(Zr,Ti)O 3 (PZT), polyvinylidene fluoride, etc. Host-guest crown ether inclusion complexes are a promising branch in the study of molecular ferroelectrics. Compared with ceramic ferroelectrics and organic-inorganic hybrid perovskite ferroelectrics, they generally have flexible structures. In this scheme, by introducing polar-chiral histidine as a guest molecule, it has the advantages of good biocompatibility and environmental protection compared with traditional aniline guest molecules.
[0024] Third, the present invention introduces L-, D- and DL-histidine cations into the crown ether system, and develops three amino acid crown ether inclusion complexes based on 18-crown-6, which solves the limitations of the prior art in chiral recognition and piezoelectric material applications. Traditional piezoelectric and ferroelectric materials are usually insensitive to the response of chiral molecules, making it difficult to achieve accurate chiral molecule recognition. In response to this problem, the present invention uses a unique molecular design to produce significant differences in ferroelectric and piezoelectric responses of histidine crown ether inclusion complexes of different chirality (L-, D- and DL-), thereby providing new materials for the development of chiral molecule recognition sensors and effectively improving the chiral recognition accuracy and reliability of the sensor.
[0025] In addition, existing piezoelectric materials are mostly made of inorganic materials or complex synthetic materials, which are easily limited by factors such as mechanical flexibility and environmental stability, making it difficult to achieve widespread promotion in applications such as wearable devices. The histidine crown ether inclusion compound provided by the present invention is prepared by a simple solution evaporation method, which is easy to operate and low in cost, and exhibits excellent mechanical flexibility and durability, and is suitable for wearable piezoelectric nanogenerators and other low-power energy collection devices. This innovation breaks through the limitations of traditional piezoelectric materials and provides effective material support for the energy supply of portable and flexible electronic devices.
[0026] In terms of piezoelectric and ferroelectric properties, the inclusion compound of the present invention has significant response differences under different chiral conditions, especially in the DL-histidine inclusion compound, due to the coexistence of L- and D-enantiomers, the disorder effect within the molecule is enhanced, resulting in the partial offset of the piezoelectric and ferroelectric responses between molecules. This characteristic significantly improves the difference in ferroelectric and piezoelectric properties of the inclusion compound, providing new possibilities for future applications in ferroelectric recognition and high-sensitivity sensors, and helping to develop sensor devices with higher accuracy and faster response speed.
[0027] In general, the present invention significantly improves the application performance of materials in the fields of chiral recognition, low-power device energy supply and sensing through a unique chiral strategy and crown ether-amino acid inclusion complex design, and has significant innovation and superiority compared to the existing technology. Through structural innovation and efficient synthesis methods, the present invention provides an important material foundation for the technological progress of related industries, and is expected to promote the further development of flexible electronics, sensor recognition and environmentally friendly power generation equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the chiral regulation strategy of compound 1-3 provided in the embodiment of the present invention;
[0029] Figure 2 Compound 1 provided in an embodiment of the present invention (a) has a simplest structure diagram, (b) has a one-dimensional chain diagram, and (c) has a chiral atom in the chain diagram; Compound 2 (d) has a simplest structure diagram, (e) has a one-dimensional chain diagram, and (f) has a chiral atom in the chain diagram; Compound 3 (g) has a simplest structure diagram, (h) has a one-dimensional chain diagram, and (i) has a chiral atom in the chain diagram;
[0030] Figure 3 The following are compound 1-3 provided in the examples of the present invention: (a) infrared spectrum; (b) UV-visible absorption spectrum; (c) circular dichroism spectrum; (d) TG curve; (e) 13 C-NMR spectrum; (f) PE hysteresis loop; (g) voltammetric curve;
[0031] Figure 4(a)-(c) Hirshfeld surface images and fingerprint images of compound 1 provided in the embodiments of the present invention; (d)-(f) Hirshfeld surface images and fingerprint images of compound 2; (g)-(i) Hirshfeld surface images and fingerprint images of compound 3;
[0032] Figure 5 Compound 1 provided in an embodiment of the present invention (a) dielectric image at elevated temperature, (b) dielectric image at reduced temperature-elevated cycle, (c) dielectric switch; Compound 2 (d) dielectric image at elevated temperature, (e) dielectric image at reduced temperature-elevated cycle, (f) dielectric switch; Compound 3 (g) dielectric image at elevated temperature, (h) dielectric image at reduced temperature-elevated cycle, (i) dielectric switch;
[0033] Figure 6 It is a simulation diagram of the experimental process provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] like Figure 1 As shown, the present invention uses a chiral strategy to introduce L-, D- and DL-histidine cations into the crown ether system to obtain three amino acid crown ether inclusion complexes based on 18-crown-6 [L-His-OMe] 2+ (18-crown-6)[CoCl 4 ] 2- (1, L-His-OMe = L-histidine methyl ester), [D-His] 2+ [(18-crown-6)(H 2 O)][CoCl 4 ] 2- (2, D-His = D-histidine) and [DL-His] 2+ (18-crown-6)[CoCl 4 ] 2-(3, D-His = D-histidine), all three have good piezoelectric properties and potential ferroelectricity. Through variable temperature X-ray single crystal diffraction, it can be seen that only L- or D-His exists in compounds 1 and 2, while L- and D-His exist simultaneously in compound 3, inducing disorder in the molecule. And because DL-His contains both L- and D-His, the intermolecular forces, ferroelectricity and piezoelectricity of compound 3 will be "offset" to a certain extent compared with compounds 1 and 2. This obvious difference in piezoelectric and ferroelectric properties between enantiomers and racemates may play an important role in future ferroelectric recognition or sensing.
[0036] The embodiment of the present invention provides a method for constructing a histidine piezoelectric material through a chiral strategy, and a blue compound 1-3 is obtained by natural evaporation from a methanol aqueous solution;
[0037] Compound 1 is [L-His-OMe] 2+ (18-crown-6)[CoCl 4 ] 2- ;
[0038] Compound 2 is [D-His] 2+ [(18-crown-6)(H 2 O)][CoCl 4 ] 2- ;
[0039] Compound 3 is [DL-His] 2+ (18-crown-6)[CoCl 4 ] 2- .
[0040] The synthesis method of compound 1 is as follows: 234 mg (1.51 mmol) of L-histidine, 400 mg (1.51 mmol) of 18-crown ether and CoCl 2 6H 2 360 mg (1.51 mmol) of O was dissolved in 10 mL of methanol, 5 mL of methanol and 10 mL of methanol respectively, and then 1 mL of hydrochloric acid (mass fraction 36.5%) was added dropwise to the L-histidine and cobaltous chloride mixed solution for acidification, and the acidified mixed solution was sonicated until the solution was clear, and then the cobaltous chloride mixed solution and the 18-crown ether-6 mixed solution were added dropwise to the L-histidine mixed solution respectively, and then the mixed solution was placed at room temperature and waited for natural evaporation, and blue strip crystals 1 were obtained after 7 days;
[0041]
[0042] The synthesis method of compound 2 is as follows: 234 mg (1.51 mmol) of D-histidine, 400 mg (1.51 mmol) of 18-crown ether and CoCl 2 6H 2 360 mg (1.51 mmol) of O was dissolved in 10 mL of methanol, 5 mL of methanol and 10 mL of methanol respectively, and then 1 mL of hydrochloric acid (mass fraction 36.5%) was added dropwise to the mixed solution of D-histidine and cobaltous chloride respectively for acidification. The acidified mixed solution was sonicated until the solution was clear, and then the cobaltous chloride mixed solution and the 18-crown ether-6 mixed solution were added dropwise to the D-histidine mixed solution respectively, and then the mixed solution was placed at room temperature and waited for natural evaporation. After 7 days, blue strip crystals 2 were obtained;
[0043]
[0044] The synthesis method of compound 3 is as follows: 234 mg (1.51 mmol) of DL-histidine, 400 mg (1.51 mmol) of 18-crown ether and CoCl 2 6H 2 O 360mg (1.51mmol) was dissolved in 10mL methanol, 5mL methanol and 10mL methanol respectively, and then 1mL hydrochloric acid (mass fraction 36.5%) was added dropwise to the mixed solution of DL-histidine and cobaltous chloride respectively for acidification, and the acidified mixed solution was sonicated until the solution was clear, and then the cobaltous chloride mixed solution and the 18-crown ether-6 mixed solution were added dropwise to the DL-histidine mixed solution respectively, and then the mixed solution was placed at room temperature and waited for natural evaporation, and blue strip crystals 3 were obtained after 7 days;
[0045]
[0046] Infrared spectrum (4000-400cm -1 ) was measured by a Thermo Scientific Nicolet Is5 Fourier transform infrared spectrometer; thermogravimetric analysis was performed by an American TA Q50 thermogravimetric analyzer with Al 2 O 3As a reference, the test was carried out in the temperature range of 300K-820K at a heating rate of 10K / min under flowing nitrogen; the DSC measurement was carried out at atmospheric pressure by a TAQ20 instrument under nitrogen protection, in the temperature range of 210-280K, with a heating rate of 10K / min, and the samples were tested during heating and cooling. The dielectric constant was tested by Tonghui TH 2828 impedance analyzer in the frequency range of 500 Hz to 1 MHz, 1.0 V voltage and 2 K / min temperature scanning rate. The specific method was that the compound 1-3 samples were pressed into tablets and then coated with conductive silver paste on both sides. After being placed at room temperature for 2 h (dried), the temperature-dependent dielectric constant was tested under the above conditions. The elemental analysis was obtained by German ArialFontVarioEL elemental analyzer. The ferroelectric properties of the crystal samples were measured using a Radiant PremierⅡ ferroelectric tester, and the polarization-electric field (PE) hysteresis loops were recorded at different temperatures. The electrochemical test was carried out using a CHI700E electrochemical workstation. After the sample and carbon black were mixed and ground and loaded, the capacitance-voltage characteristic curve (CV curve) at different scanning rates was tested using a three-electrode system, that is, a glassy carbon loaded electrode was used as the working electrode, a saturated calomel electrode was used as the reference electrode, and a platinum wire electrode was used as the counter electrode. At 0.1 mol / L H 2 SO 4 and 0.5 mol / L Na 2 SO 4 Measured in mixed solution.
[0047] Select transparent single crystals of moderate size, smooth surface and regular shape, place them on a single crystal X-ray diffractometer at room temperature (293K) and low temperature (100K), and test and analyze them by graphite monochromatized Mo-Kα rays (λ=0.071073nm). In the crystal analysis process, the Patterson method and direct method are used to determine the position of atoms, the coordinates of non-hydrogen atoms are determined by the least squares method, and the parameter anisotropy of F2 is refined using the SHELXTL program, and finally the crystallographic parameters of compounds 1-3 are obtained, as shown in Table 1.
[0048] Table 1 Crystallographic parameters of compounds 1-3
[0049]
[0050]
[0051] a R 1 =∑(|F o |-|F c |) / ∑|F o |; b w R2 =[∑w(|F o | 2 -|F c | 2 ) 2 / ∑w(F o 2 )] 1 / 2
[0052] Piezoelectricity refers to the phenomenon that certain materials generate electric charge when subjected to mechanical stress. This property enables piezoelectric materials to directly convert mechanical energy into electrical energy, which breaks through the limitations of traditional battery capacity and life. Therefore, this type of power source is considered a promising candidate in implantable medical devices, portable electronic devices, and flexible wearable smart terminals. Crown ether supramolecular rotators, as an important branch of artificial molecular machines, have attracted great attention from researchers in the fields of physics, chemistry, energy, and biomedicine. More importantly, this stator-rotor structure facilitates energy conversion processes, such as the conversion between thermal energy and kinetic energy, and the conversion between mechanical energy and electrical energy. Benefiting from the structural diversity and tunability of the crown ether-based supramolecular family, the piezoelectric properties of existing crown ether molecules can be significantly improved by optimizing the chemical modification strategy given by screening different organic cations and inorganic anions and assembling them with crown ether molecules. For example, Li et al. reported that [(histamine)(18-crown-6) 2 ](BF 4 ) 2 By doubly protonating histamine and increasing [(histamine)(18-crown-6)](BF 4 ) successfully endowed with piezoelectricity. Recently, based on H / F substitution, Lv and colleagues revealed a crown ether-based supramolecular rotator that achieved a piezoelectric coefficient d 33 The significant enhancement is more than 40 times greater than that of non-fluorinated compounds. Under the guidance of crystallographic engineering, Fu et al. have developed a crown ether-based ferroelastic supramolecular rotator [(N,N-dimethylethylethylenediamine)(18-crown-6)]BF 4 ] has made a breakthrough, successfully realizing an energy harvesting device for the first time to evaluate its potential as a piezoelectric self-powered device, and successfully lighting up an LED (light-emitting diode) by collecting mechanical energy. This work has taken an important step towards artificial supramolecular machines and has aroused widespread interest in self-powered flexible devices. On this basis, the present invention has designed this technical solution and introduced chiral amino acids into the crown ether inclusion system for the first time, designing and synthesizing a crystalline material with good piezoelectric and ferroelectric properties.
[0053] The present invention uses L-histidine, D-histidine and DL-histidine, 18-crown ether-6 and cobaltous chloride as raw materials, and conducts repeated tests in a mixed solution of methanol and hydrochloric acid. It is found that the crystal form of compound 1-3 is the best under the ratio of 2:2:2 and infrared peaks are detected. Process simulation is as follows Figure 6 As shown, according to the experimental results, the crystal appearance of compounds 1-3 is blue strip-shaped. Although the space groups of the three are different, they all belong to the ferroelectric space group. The crystallographic parameter table of compounds 1-3 (Table 1) can also confirm this.
[0054] Crystal structure analysis
[0055] The variable temperature single crystal structures of compounds 1-3 were determined at 100K (LTP) and 293K (RTP) respectively, aiming to reveal the changes in the microstructure. Table 1 is a table of crystallographic parameters of compounds 1-3. Figure 2 It can be seen that compound 1 is monoclinic at LTP and RTP, while compounds 2 and 3 are orthorhombic, and the space group of compound 1 is P2 1 (polar-ferroelectric space group), compound 2 has a space group of P2 1 2 1 2 1 (polar-ferroelectric space group), compound 3 has a space group of Pna2 1 (Polar-ferroelectric space group). From 100K to 293K, compound 1, a increased by 0.8%, b increased by 0.6%, c increased by 0.8%, V increased by 2.4%, α, γ and Z did not change, β decreased by 0.5%. From 100K to 293K, compound 2, a increased by 2.1%, b increased by 2.1%, c decreased by 1.6%, V increased by 2.6%, α, β, γ and Z did not change. From low temperature to room temperature, compound 3, a increased by 1.5%, b decreased by 0.04%, c increased by 1.29%, V increased by 2.8%, α, β, γ and Z did not change. From the changes of compounds 1-3 with temperature, it can be seen that from LTP and RTP, the atomic displacement parameters basically show an increasing trend, indicating that with the increase of temperature, the molecular thermal motion becomes more intense. And although the space groups of the three compounds have not changed, their unit cell parameters such as bond length and bond angle have changed to a certain extent, indicating that compounds 1-3 have isostructural phase transitions within the range of LTP and RTP.
[0056] The main histidine molecules constituting compounds 1-3 are enantiomers, so their simplest structures are also different. Figure 2 As shown in (a), (d) and (g), the simplest structure of compound 1 at LTP and RTP consists of a methyl-esterified L-His 2+ The cation (-COOH on L-His and solvent CH3 OH undergoes esterification to form L-His-OMe), an 18-crown-6 molecule, and a [CoCl 4 ] 2- anion, all atoms are completely ordered at low temperature and room temperature; the simplest structure of compound 2 at LTP and RTP consists of a protonated D-His 2+ cation, a 18-crown-6 molecule, a free water molecule, and a [CoCl 4 ] 2- Anionic composition, all atoms are completely ordered at low temperature and room temperature. 2+ The cations, free water molecules and 18-crown ether-6 molecules form supramolecular motor-type cations through NH···O and OH···O hydrogen bonds. The inorganic metal complex [CoCl 4 ] 2- The anion acts as a charge balancer. The structure of compound 3 is very similar to compound 2, but there are also some differences. The simplest structure of compound 3 at LTP and RTP includes a protonated DL-His 2+ cation, an 18-crown-6 molecule and a [CoCl 4 ] 2- Anionic group composition, DL-His at low temperature and room temperature 2+ The C13, C14, O7 and O8 atoms on the cation are split into two occupied positions, namely C22, COOD, O7A and O8A; the C atoms and O atoms on the 18-crown-6 molecule each occupy two atomic positions, and the occupancy rates of different atoms are different, and DL-His 2+ The cation also forms a supramolecular motor-type cation with the 18-crown ether-6 molecule through NH···O hydrogen bonds. The one-dimensional chain diagram of compounds 1-3 is shown in the figure. In compound 1, [L-His-OMe] 2+ Facing two different directions, [CoCl 4 ] 2- The anionic groups are arranged in it to form an integral unit and are repeated to form a one-dimensional chain structure ( Figure 2 (b)), Figure 2 (c) is to combine the [L-His-OMe] 2+ The supramolecular complex cation is enlarged separately, and it can be seen that the rotors in the rotor-stator structure formed by the main body 18-crown ether-6 and the guest histidine in the upper and lower layers are L-His; the chain diagram of compound 2 is similar to that of compound 1, and [D-His] 2+ Also facing two different directions, [CoCl 4 ]2- The anionic groups are arranged in it to form an integral unit and are repeated to form a one-dimensional chain structure ( Figure 2 (e)), the [D-His] 2+ The supramolecular complex cation is magnified separately, and it can be seen that the rotors in the rotor-stator structure formed by the host 18-crown ether-6 and the guest histidine in the upper and lower layers are both D-His ( Figure 2 (f)); Compound 3 is slightly different from compounds 1 and 2. In the chain diagram, [DL-His] 2+ Also facing two different directions, [CoCl 4 ] 2- The anionic groups are also arranged in it to form an integral unit and are repeated to form a one-dimensional chain structure ( Figure 2 (h)), but the [DL-His] 2+ When the supramolecular complex cation is enlarged separately, it can be found that the rotors in the rotor-stator structure formed by the main body 18-crown ether-6 and the guest histidine in the upper and lower layers are staggered with D-His and L-His, indicating that both D-His and L-His components exist in compound 3 ( Figure 2 (i)).
[0057] Select appropriate amount of compound 1-3 samples and mix with dry KBr, and then measure the concentration of compound 1-3 at 4000-500 cm -1 Infrared testing is performed within the fluctuation range, such as Figure 3 As shown in (a), compound 1 has a peak at 3265-3017 cm -1 and 1746cm -1 The characteristic peaks at 3 + and C=O group stretching vibration peaks, 1098, 961, 827 cm -1 The strong absorption peak of compound 2 is the vibration peak of the -COC- group in 18-crown-6. Therefore, it is preliminarily inferred that compound 1 may contain two active ingredients, L-His and 18-crown-6. -1 The broad and intense peaks on the left and right are the stretching vibration peaks of -OH in free water, 3290-3020cm -1 and 1750cm -1 The characteristic peaks at 3 + and C=O group stretching vibration peaks, with wavelengths at 1100, 959, and 833 cm -1The strong absorption peak of compound 3 is the vibration peak of -COC- group in 18-crown-6. Therefore, it is preliminarily inferred that compound 2 may contain three active ingredients: D-His, 18-crown-6 and free water. -1 The relatively weak broad peaks on the left and right are the stretching vibration peaks of -OH on the carboxyl group, 3300-2970cm -1 and 1740cm -1 The characteristic peaks at 3 + and C=O group stretching vibration peaks, with wavelengths at 1100, 959, and 837 cm -1 The strong absorption peak is the vibration peak of the -COC- group in 18-crown-6. Therefore, it is preliminarily speculated that compound 3 may contain two active ingredients, DL-His and 18-crown-6.
[0058] In order to prove the existence of chiral structure, solid circular dichroism analysis was performed on compounds 1-3. When observing the absorption spectrum, it was found that the ultraviolet visible absorption spectrum (UV-Vis) spectrum and Fourier transform infrared spectrum (FT-IR) spectrum of the three compounds showed almost the same characteristics ( Figure 3 (a) and 3(b)). The chiral characteristics were further investigated by room temperature circular dichroism (CD) spectroscopy in the UV-visible absorption range. KBr powder pellets were used during CD measurements to detect the CD signals of strong samples, such as Figure 3 (c) shows the enantiomer [L-His-OMe] 2+ (18-crown-6)[CoCl 4 ] 2- and [D-His] 2+ [(18-crown-6)(H 2 O)][CoCl 4 ] 2- The mirror-symmetric CD signal at 220 nm and the good correspondence between the CD response and the UV / Vis spectrum indicate that the two crown ether compounds with homochiral histidine cations have optical bistability; while the racemic [DL-His] 2+ (18-crown-6)[CoCl 4 ] 2- Basically no CD signal was detected in the UV-visible absorption range, which may be because it contains equal amounts of left-handed (L-His) and right-handed (D-His) isomers, and theoretically their net optical activity should be zero, so a very small or zero absorption peak will be shown in the circular dichroism spectrum.
[0059] In order to further study the thermal properties of compounds 1-3, thermogravimetric analysis was performed on them. Figure 4 (d) It can be seen that compounds 1-3 did not decompose before 400K, indicating that the compounds were relatively stable within this temperature range, and the TG curves of the three were very similar, indicating that compounds 1-3 were crystalline materials with similar structures and good thermal stability. Figure 3 (e) is compound 1-3 at room temperature 13 C-NMR spectrum, by Figure 3 It can be seen that 13 The peaks at 65 ppm and 200 ppm in the C-NMR spectrum belong to CH 2 The C=O group in the group and His, among which compounds 1 and 2 have only one peak in both places, indicating that there is only one C atom in one chemical environment in the C=O group on the 18-crown-6 molecule and the L-His and D-His molecules in compounds 1 and 2, while compound 3 has two split peaks in both places, indicating that there are C atoms in two chemical environments in these two places in compound 3, further proving the disorder of its crown ether molecules and DL-His at room temperature.
[0060] Ferroelectric tests were performed on compounds 1-3 to obtain PE hysteresis loops such as Figure 3 As shown in (f), compounds 1-3 undergo ferroelectric phase transition at 193K. Although compounds 1-3 have the same ferroelectric phase transition temperature, their spontaneous polarization values (Ps) are quite different. L-histidine has the largest polarization value of 0.127 μC / cm 2 ; followed by D-histidine, which is 0.0830μC / cm 2 DL-histidine has the smallest polarization value, which is 0.0557μC / cm 2 . Therefore, the introduction of chiral amino acids into the molecular system can directly design molecular ferroelectrics, and the obvious difference in ferroelectric properties between its enantiomers and racemates may play an important role in future ferroelectric recognition or sensing. Compounds 1-3 were electrochemically tested at a scan rate of 0.5 V / s. The cyclic voltammetry (CV) test results showed that compounds 1-3 had a pair of obvious reversible redox peaks in the potential range of -800-0 mV ( Figure 3 (g)), and when the scanning rate is 0.5 V / s, the half-peak potential E 1 / 2 Almost the same, all around 450mV (E 1 / 2 =(E Pa +E Pc ) / 2). In summary, it can be judged that the redox peak corresponds to the anion group [CoCl 4 ] 2- Medium 2+ / Co+ The electron transfer during electrolysis is good, and the CV curves have a high overlap after the cycle.
[0061] In order to further analyze the effect of intermolecular interactions between enantiomers and racemates, the Hirshfeld d of the histidine supramolecular cations in compounds 1-3 was calculated and evaluated using CrystalExplorer software. norm Surfaces, specifically Hirshfeld surfaces, are shown in red-white-blue, indicating intermolecular contacts shorter (red), surrounding (white), and longer (blue) than van der Waals forces. Figure 4 The difference in the red dot area on the Hirsfield surface diagram of compounds 1-3 indicates that the interaction between the His cation and the surrounding molecules has changed, that is, compounds 1 and 2 have more abundant hydrogen bonds than compound 3 at 293K. It can be inferred from the percentage of each hydrogen bond that NH···O and OH···O are the main interactions, resulting in the appearance of the red concave part, where the percentage of compound 1 decreases from 49.0% of H···H to 32.3% of compound 2, and then increases to 42.9 in compound 3; d norm The decrease from 0.6074 in compound 1 to 0.4684 in compound 2 and then to 0.4235 in compound 3 indicates that the contact between cations in compound 1 is the strongest, which greatly increases the motion barrier of cations, followed by compound 3, and the intermolecular force of compound 2 is the weakest. The results show that the coexistence of L-His and D-His in racemic compound 3 will produce a certain "offsetting" effect on its intermolecular force and thermal motion.
[0062] As a temperature-dependent function, the dielectric constant usually shows a significant mutation near the phase transition temperature. Figure 5 As shown, the temperature-dependent dielectric properties of compounds 1-3 along the a-axis were measured in the temperature range of 165-300K and the frequency range of 500Hz to 1MHz. As shown in the figure, dielectric anomalies with a "λ"-shaped peak were detected near 220K for compounds 1-3 during the heating process, and the dielectric constant curves of compounds 1-3 showed similar temperature-dependent curves in the entire temperature range, which may be caused by the similarity between their molecular structures ( Figure 5(a) and 5(d) and 5(g)); for compounds 1-3, during the cooling process, their dielectric constants are basically stable at 300K-240K, and slowly decrease after 240K, and the dielectric constant presents a step-like shape; during the heating process, when the temperature is 160-220K, the dielectric constants of the three increase slowly. When the temperature exceeds 220K, the dielectric constant growth rate increases significantly, showing a "λ" growth, and reaches a peak at around 240K. Subsequently, the dielectric constant of compound 1 shows a small peak again at around 260K and tends to be stable, while the dielectric constants of compounds 2 and 3 decrease directly and gradually become flat. It can also be found that the temperature at which the dielectric anomaly of compounds 1-3 occurs during cooling and heating is roughly the same, which is basically consistent with the temperature at which the ferroelectric phase transition occurs, indicating that compounds 1-3 have cyclically reversible dielectric properties and obey the Curie-Veiss law well, with obvious dielectric anomalies appearing near the phase transition temperature ( Figure 5 (b) and 5(e) and 5(h)). It is worth noting that as the temperature changes periodically, the dielectric signal intensity of compounds 1-3 remains almost constant after 6 cycles, indicating that the dielectric signal of the switch made of compounds 1-3 is stable after multiple cycles, verifying its dielectric stability ( Figure 5 (c) and 5(f) and 5(i)).
[0063] Crystals have polar space group structures, which usually means that there are orderly arranged polar molecules or ions in the crystals. These polar arrangements will cause the atoms or molecules of the crystals to rearrange when subjected to external stress, resulting in charge separation. This phenomenon is called the piezoelectric effect and is reflected in the ability to convert between force and electricity. Piezoelectric force microscopy (PFM) is a very useful method for studying the static and dynamic properties of ferroelectric domains. As a non-destructive and visual method, it has long been used to characterize piezoelectricity and ferroelectricity at the nanoscale, and domain walls can be switched by applying an external electric field. The relative strength of the piezoelectric coefficient and the direction of domain polarization can be obtained simultaneously from the amplitude and phase mapping of the PFM signal, respectively. Figure 6The static domain structure along the a-axis direction in bulk single crystals of compounds 1-3 is shown, where there is a strong signal in the perpendicular PFM mode, while the lateral PFM response is negligible. It can be clearly seen from the phase image that clear domain patterns and domain walls can be observed in both samples of compounds 1 and 2, and there is no correlation between the domain pattern and the surface morphology, indicating that there are spontaneous polarizations in different directions in the two samples; and there are two antiparallel domains with obvious contrast (about 180°) in compound 3. In addition, by superimposing the perpendicular PFM phase and amplitude on the three-dimensional (3D) morphology, it can be seen that there is no crosstalk between the sample morphology and the PFM signal. Therefore, these results prove the existence of ferroelectric domains and 180° domain walls in single crystals of compounds 1-3. In addition, PFM is also a method that can quantify local piezoelectric properties, where the good linearity between the driving voltage and amplitude can provide solid evidence for the piezoelectric effect. The bipolar piezoelectric hysteresis loop of the PFM phase signal and the typical butterfly loop of the amplitude signal prove the switching of ferroelectric polarization in compound 1-3 single crystals. The obvious 180° reversal of the phase signal and the typical butterfly-shaped amplitude loop show obvious ferroelectric polarization switching, which once again proves the ferroelectricity of compounds 1-3.
[0064] Example 1: Application of ferroelectric recognition sensor
[0065] By applying the three histidine crown ether inclusion compounds (Compound 1, Compound 2, Compound 3) of the present invention to ferroelectric recognition sensors, the recognition of molecules with different chirality can be effectively achieved. Compounds 1 and 2 contain a single chiral histidine (L or D type), while Compound 3 contains both L and D enantiomers, and therefore exhibits different electrical response behaviors in piezoelectric and ferroelectric properties. Utilizing this characteristic, the recognition of chiral molecules can be achieved by measuring the difference in the ferroelectric and piezoelectric responses of the material. In specific applications, after the sensor comes into contact with histidine of different chirality, it can identify L-, D- or DL-histidine by detecting the change in its ferroelectric hysteresis loop. In addition, by selecting appropriate electrochemical test conditions, the sensitivity and recognition accuracy of the sensor can be further improved. This application can meet the needs for the recognition of chiral substances in the fields of biomedicine, food safety, chemical analysis, etc., and provide new materials for the field of chiral molecular sensors.
[0066] Example 2: Wearable piezoelectric nanogenerator
[0067] Utilizing the good piezoelectric properties of the three amino acid crown ether inclusion compounds in the present invention, these materials can be integrated into wearable piezoelectric nanogenerators to collect mechanical energy generated by human body movement and convert it into electrical energy. In particular, compound 1 and compound 2, due to their excellent piezoelectricity, can be used as sensitive element materials and embedded in wearable devices (such as smart watches and sports bracelets). When these devices are squeezed or bent, the piezoelectric effect of the material will generate electrical signals, which will be stored through an external circuit or used to drive small electronic devices. This technology can meet the energy supply needs of low-power electronic products in daily activities, and is expected to serve as an important technical support for self-powered wearable devices in the future. In addition, based on the durability and environmental protection characteristics of the material, the system can operate stably in harsh environments such as high cold and humidity, and is a key material choice for future low-power portable devices.
[0068] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A histidine crown ether-based piezoelectric material [L-His-OMe] 2+ (18-crown-6)[CoCl4] 2- , characterized in that, [L-His-OMe] 2+ (18-crown-6)[CoCl4] 2- The structural formula is:
2. A histidine crown ether-based piezoelectric material [L-His-OMe] as claimed in claim 1 2+ (18-crown-6)[CoCl4] 2- The preparation method is characterized in that The following steps are involved: 234 mg of 1.51 mmol L-histidine, 400 mg of 1.51 mmol 18-crown-6 and 360 mg of CoCl2·6H2O were dissolved in 10 mL of methanol, 5 mL of methanol and 10 mL of methanol, respectively. Then, 1 mL of hydrochloric acid with a mass fraction of 36.5% was added dropwise to the mixed solution of L-histidine and cobaltous chloride for acidification. The acidified mixed solution was sonicated until the solution was clear. Then, the cobaltous chloride mixed solution and the 18-crown-6 mixed solution were added dropwise to the L-histidine mixed solution in sequence. The mixed solution was placed at room temperature and waited for natural evaporation. After 7 days, blue strip crystals 1 were obtained.
3. A histidine crown ether-based piezoelectric material [D-His] 2+ [(18-crown-6)(H2O)][CoCl4] 2- , characterized in that, [D-His] 2+ [(18-crown-6)(H2O)][CoCl4] 2- The structural formula is:
4. A method for preparing the histidine crown ether-based piezoelectric material [D-His]2+[(18-crown-6)(H2O)][CoCl4]2- as claimed in claim 3, characterized in that: The following steps are involved: 234 mg of 1.51 mmol D-histidine, 400 mg of 1.51 mmol 18-crown-6 and 360 mg of 1.51 mmol CoCl2·6H2O were dissolved in 10 mL of methanol, 5 mL of methanol and 10 mL of methanol, respectively. Then, 1 mL of hydrochloric acid with a mass fraction of 36.5% was added dropwise to the mixed solution of D-histidine and cobaltous chloride for acidification. The acidified mixed solution was sonicated until the solution was clear. Then, the cobaltous chloride mixed solution and the 18-crown-6 mixed solution were added dropwise to the D-histidine mixed solution in sequence. The mixed solution was placed at room temperature and waited for natural evaporation. After 7 days, blue strip crystals 2 were obtained.
5. A histidine crown ether-based piezoelectric material [DL-His] 2+ (18-crown-6)[CoCl4] 2- , characterized in that, [DL-His] 2+ (18-crown-6)[CoCl4] 2- The structural formula is:
6. A histidine crown ether-based piezoelectric material [DL-His] as claimed in claim 5 2+ (18-crown-6)[CoCl4] 2- The preparation method is characterized in that The following steps are involved: 234 mg of 1.51 mmol DL-histidine, 400 mg of 1.51 mmol 18-crown-6 and 360 mg of 1.51 mmol CoCl2·6H2O were dissolved in 10 mL of methanol, 5 mL of methanol and 10 mL of methanol, respectively. Then, 1 mL of 36.5% hydrochloric acid was added to the mixed solution of DL-histidine and cobaltous chloride for acidification. The acidified mixed solution was sonicated until the solution was clear. Then, the cobaltous chloride mixed solution and the 18-crown-6 mixed solution were dropped into the DL-histidine mixed solution in sequence. The mixed solution was placed at room temperature and waited for natural evaporation. After 7 days, blue strip crystals 3 were obtained.